AdeIJK, a Resistance-Nodulation-Cell Division Pump Effluxing Multiple Antibiotics in Acinetobacter baumannii - Damier-Piolle, Laurence (American Society for Microbiology (ASM), 2008)
We have identified a second resistance-nodulation-cell division (RND)-type efflux pump, AdeIJK, in clinical isolate Acinetobacter baumannii BM4454. The adeI, adeJ, and adeK genes encode, respectively, the membrane fusion, RND, and outer membrane components of the pump. AdeJ belongs to the AcrB protein family (57% identity with AcrB from Escherichia coli). mRNA analysis by Northern blotting and reverse transcription-PCR indicated that the genes were cotranscribed. Overexpression of the cloned adeIJK operon was toxic in both E. coli and Acinetobacter. The adeIJK genes were detected in all of the 60 strains of A. baumannii tested. The two latter observations suggest that the AdeIJK complex might contribute to intrinsic but not to acquired antibiotic resistance in Acinetobacter. To characterize the substrate specificity of the pump, we have constructed derivatives of BM4454 in which adeIJK (strain BM4579), adeABC (strain BM4561), or both groups of genes (strain BM4652) were inactivated by deletion-insertion. Determination of the antibiotic susceptibility of these strains and of BM4652 and BM4579, in which the adeIJK operon was provided in trans, indicated that the AdeIJK pump contributes to resistance to β-lactams, chloramphenicol, tetracycline, erythromycin, lincosamides, fluoroquinolones, fusidic acid, novobiocin, rifampin, trimethoprim, acridine, safranin, pyronine, and sodium dodecyl sulfate. The chemical structure of these molecules suggests that amphiphilic compounds are the preferred substrates. The AdeABC and AdeIJK efflux systems contributed in a more than additive fashion to tigecycline resistance.